Perceived Quality, Cost, and Repurchase Intentions in Luxury Goods: The Mediating Role of Perceived Value Among Chinese Consumers - Liang, Liu; Yiwei, Lu; Yujie, Zhao (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
Using structural equation modeling (SEM) analysis of 403 customers, this research aims to analyze the repurchase intention of customers in Chinese jewelry and art enterprises based on the theories of perceived value, perceived quality, and perceived cost. A theoretical model was developed to investigate whether repurchase intention is influenced by functional, social, and emotional value mediated by perceived quality and perceived cost. We analyzed data using SPSS and structural equation modeling (SEM) to test the hypotheses. The results indicate that functional value (β = 0.313, p < 0.001), emotional value (β = 0.334, p < 0.001), and social value (β = 0.213, p < 0.001) significantly impact customers’ repurchase intention, with emotional value demonstrating the strongest predictive power. For practitioners, prioritizing emotional branding strategies may enhance customer loyalty more effectively than focusing solely on social value. We discuss managerial implications and future research directions. This study contributes to the growing literature on luxury consumption in emerging markets by providing cultural-specific insights for the Chinese context, particularly highlighting the evolving nature of consumer behavior in post-pandemic luxury markets.